Azo dye adsorption on an industrial waste-transformed hydroxyapatite adsorbent: Kinetics, isotherms, mechanism and regeneration studies. Issue 3 (June 2020) - Bensalah, Hiba; Younssi, Saad Alami; Ouammou, Mohamed; Gurlo, Aleksander; Bekheet, Maged F.
Graphical abstract: Highlights: Converting phosphogypsum waste into hydroxyapatite nanorods by hydrothermal method. The obtained hydroxyapatite nanorods exhibit high surface area of 135 m 2 /g. The obtained materials were found to be effective adsorbents for Congo red (CR) dye. Hydroxyapatite adsorbent shows a maximum adsorbed quantity of 139 mg/g for CR. This study offers benefits for both waste management and wastewater treatment. Abstract: Nanocrystalline hydroxyapatite (HAp) with high surface area was synthesized by surfactant-assistant hydrothermal method from an industrial waste phosphogypsum. X-ray diffraction (XRD), transmission electron microscopy (TEM) and nitrogen sorption characterizations revealed that HAp crystals grow as needle-like particles along the c direction with surface area of 86 and 135 m 2 /g for the samples synthesized without and with Brij-93 surfactant, respectively. Adsorption of anionic azo dye Congo Red (CR) were conducted on both samples, taking into account the influence of initial dye concentration (100–500 mg/L), adsorbent dosage (0.5–30 g/L), contact time (5–180 min) and solution pH (2–12). Kinetic studies showed that the adsorption of CR followed pseudo-second-order model, i.e., chemisorption is the rate controlling step. Freundlich isotherm was found to be most suitable model for the adsorption of CR, i.e. adsorption is multilayer process. The calculated maximum adsorption capacity of synthesized B93-HAp adsorbent using Brij-93 surfactant was found to be 139 mg/g at pH 5.5 and dosage of 2 g/L. Two predominant mechanisms were observed for CR adsorption, electrostatic attraction and hydrogen bonding as revealed by Fourier transformed infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) studies. The multi-cycle sorption/desorption tests indicated that waste-transformed adsorbent could be regenerated and reused up to 6 cycles. Therefore, this work shows that the conversion of waste materials into adsorbents has a two-fold environmental benefit for both waste management and wastewater treatment.